2018
DOI: 10.1021/acs.macromol.8b02022
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphazenes and Cyclotriphosphazenes with Propeller-like Tetraphenylethyleneoxy Side Groups: Tuning Mechanical and Optoelectronic Properties

Abstract: A new class of polyphosphazene elastomers has been synthesized that combines a −PN– backbone with both 2,2,2-trifluoroethoxy and tetraphenyl­ethyleneoxy (TPEO) side groups. The polymer syntheses and photoproperties were first modeled using small molecule cyclic phosphazenes, and these were then applied to the high polymers. The TPEO groups confer useful mechanical and photophysical properties on the polymers. Thus, those polyphosphazenes with the more rigid bidentate TPEO side groups have higher fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This exerts a significant effect on the overall properties of the polymeric product 19 . Recently, we also reported that rigid conjugated side groups interconnect with each other via steric and intermolecular pi–pi interactions, which affect the optical and physicochemical properties of the polyphosphazene 20,22–24 . In this current study, two thiophene‐based polyphosphazenes were synthesized.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…This exerts a significant effect on the overall properties of the polymeric product 19 . Recently, we also reported that rigid conjugated side groups interconnect with each other via steric and intermolecular pi–pi interactions, which affect the optical and physicochemical properties of the polyphosphazene 20,22–24 . In this current study, two thiophene‐based polyphosphazenes were synthesized.…”
Section: Introductionmentioning
confidence: 84%
“…19 Polyphosphazenes that contain other electroactive side groups have also been synthesized, and these polymers show excellent optical and electrical properties. [20][21] In a previous study, it was found that thiophene side groups attached to the backbone of a polyphosphazene can be oxidized and polymerized. This exerts a significant effect on the overall properties of the polymeric product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyphosphazene is an organic–inorganic hybrid material with many excellent properties. The research on polyphosphazene is very active, which covers many aspects such as special rubber and elastic materials, flame retardant materials, biomedical materials, and optoelectronic materials 22–26 …”
Section: Introductionmentioning
confidence: 99%